2020
DOI: 10.3390/fermentation6040105
|View full text |Cite
|
Sign up to set email alerts
|

Chestnut Shells as Waste Material for Succinic Acid Production from Actinobacillus succinogenes 130Z

Abstract: Currently, the full exploitation of waste materials for the production of value-added compounds is one of the potential solutions to lower costs and increase the sustainability of industrial processes. In this respect, the aim of this work was to evaluate the potential of chestnut shells (CSH) as substrate for the growth of Actinobacillus succinogenes 130Z, a natural producer of succinic acid that is a precursor of several bulk chemicals with diverse applications, such as bioplastics production. Hydrolysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…Batch fermentations in controlled conditions on 1-liter reactors were performed with a concentration of total sugars ranging from 30 up to 80 g/l, reaching a maximum titer of about 37 g/l in the tank. The authors found that higher total carbon source concentrations decreased the acid by-product-to-SA ratio especially in the case of glucose-based fermentations (Stylianou et al, 2020), as previously observed for A. succinogenes (Ventrone et al, 2020).…”
Section: Waste Streamssupporting
confidence: 72%
“…Batch fermentations in controlled conditions on 1-liter reactors were performed with a concentration of total sugars ranging from 30 up to 80 g/l, reaching a maximum titer of about 37 g/l in the tank. The authors found that higher total carbon source concentrations decreased the acid by-product-to-SA ratio especially in the case of glucose-based fermentations (Stylianou et al, 2020), as previously observed for A. succinogenes (Ventrone et al, 2020).…”
Section: Waste Streamssupporting
confidence: 72%
“…Citrus waste was pretreated with aqueous ammonia following the protocol described by Ventrone et al ( 2020 ). Briefly, dry biomass (5%) was incubated at 70 °C for 22 h in 10% (v/v) NH 4 OH.…”
Section: Methodsmentioning
confidence: 99%
“…(1) Alkaline hydrolysis: briefly, after size reduction in a benchtop grinder, dry biomass was dissolved in ammonium hydroxide (10% v/v) at 10% (w/v) solid loading and incubated at 70 • C for 22 h. The pH was adjusted to 7 with hydrochloric acid before biomass recovery by centrifugation and washing with water (twice). The supernatant was then discarded, and the pellet was placed in an oven at 70 • C for 24 h [26]. (2) Steam explosion (SE): the SE pre-treatment of grape stalks was conducted in a 1.5 L stirred-batch vessel made of AISI 316L.…”
Section: Biomass Pre-treatment and Hydrolysismentioning
confidence: 99%